Prioritizing the product development roadmap of Zains SAAS using Analytical Hierarchy Process (AHP) - Effendi, Yandri Marliansyah; Siallagan, Manahan Parlindungan Saragih (International Journal of Accounting and Management Information Systems, 2023)
Purpose: This study aims to prioritize the development of Zains using the Analytical Hierarchy Process (AHP). Research Methodology: This study combines FGD and survey data to prioritize Zains’ development using AHP. Key criteria include market demand, financial impact, technology, efficiency, compliance, and security. AI-powered financial insights are identified as the top development priority. Results: These findings provide insights for CNT to optimize the development of Zains and to maintain their relevance and competitiveness in the SaaS market. These recommendations are beneficial for other SaaS providers facing similar challenges. Conclusion: The study concludes that AI-powered financial insights represent the most strategically valuable development path for Zains, aligning with both market needs and internal strategic goals. Prioritizing this alternative will strengthen Zains’ position in the competitive SaaS industry and enhance its value proposition to users. Limitation: This study is limited to the perspectives of internal stakeholders within CNT and may not fully capture customer preferences or external market dynamics. Future research should incorporate customer-based evaluation and long-term performance metrics. Contribution: This research contributes to strategic decision-making in product development by integrating AHP with qualitative insights, offering a replicable framework for prioritization in the SaaS sector. It also provides a practical roadmap for Zains and similar platforms aiming to align development initiatives with organizational goals and market trends.